Collusion, torture, and inequality: Understanding the actions of the American Psychological Association as institutional betrayal. Issue 5 (19th October 2016) - Gómez, Jennifer M.; Smith, Carly P.; Gobin, Robyn L.; Tang, Shin Shin; Freyd, Jennifer J.
ABSTRACT: The Hoffman Report (Hoffman et al., 2015) documented devastating information about the American Psychological Association (APA) and the profession of psychology in the United States, prompting a public apology and a formal commitment by APA to correct its mistakes (APA, 2015). In the current article, we utilize betrayal trauma theory (Freyd, 1997), including betrayal blindness (e.g., Freyd, 1996; Tang, 2015) and institutional betrayal (Smith & Freyd, 2014b), to understand and learn from APA's behaviors. We further situate this discussion in the context of inequality, both within APA and in American society generally. We detail how the impact of APA's institutional betrayals extended beyond the organization, its members, and the psychology profession, highlighting the potential for disproportionate harm to minorities, including those who were tortured; Muslims, Middle Easterners, Afghans, and non-Americans who were not tortured; and other minority individuals (Gómez, 2015d). Acknowledging, understanding, and addressing its institutional betrayals offers APA the opportunity to take meaningful corrective and preventive measures. We propose several institutional reparations, including making concrete changes with transparency and conducting self-assessments to inform further needed changes (Freyd & Birrell, 2013). By engaging in institutional courage, APA has the potential to grow into an ethical governing body that fulfills its mission to "advance the creation, communication and application of psychological knowledge to benefit society and improve people's lives" (APA, 2016).